Colyliform Crystalline 2D Covalent Organic Frameworks (COFs) with Quasi‐3D Topologies for Rapid I2 Adsorption. Issue 50 (2nd October 2020) - Guo, Xinghua; Li, Yang; Zhang, Meicheng; Cao, Kecheng; Tian, Yin; Qi, Yue; Li, Shoujian; Li, Kun; Yu, Xiaoqi; Ma, Lijian
Abstract: Constructing three‐dimensional (3D) structural characteristics on two‐dimensional (2D) covalent organic frameworks (COFs) is a good approach to effectively improve the permeability and mass transfer rate of the materials and realize the rapid adsorption for guest molecules, while avoiding the high cost and monomer scarcity in preparing 3D COFs. Herein, we report for the first time a series of colyliform crystalline 2D COFs with quasi‐three‐dimensional (Q‐3D) topologies, consisting of unique "stereoscopic" triangular pores, large interlayer spacings and flexible constitutional units which makes the pores elastic and self‐adaptable for the guest transmission. The as‐prepared QTD‐COFs have a faster adsorption rate (2.51 g h −1 ) for iodine than traditional 2D COFs, with an unprecedented maximum adsorption capacity of 6.29 g g −1 . The excellent adsorption performance, as well as the prominent irradiation stability allow the QTD‐COFs to be applied for the rapid removal of radioactive iodine. Abstract : A novel type of COF has colyliform quasi‐three‐dimensional (Q‐3D) topologies, "stereoscopic" oblique triangular pores, and larger interlayer spacings. The Q‐3D structure improves the permeability and mass transfer rate giving a faster adsorption rate for iodine than traditional 2D COFs, and an unprecedented maximum adsorption capacity of 6.29 g g −1 .